ANALISIS PROFITABILITAS DAN SOLVABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN PADA PT ADIRA DINAMIKA MULTIFINANCE SAMARINDA - Danna Solihin, Rosa Anindaita Anggrayni Eddy Soegiarto2 (EKONOMIA, 2021)
profitability and solvency of PT. Adira Dinamika Multifinance Tbk. Samarinda branch in terms of Return On Equity, and Return On Assets in 2016-2018, to find out and analyze the level of Solvency of PT. Adira Dinamika Multifinance Tbk. Samarinda branch is reviewed from Debt to Equity, and Debt to Assets in 2016-2018.Â Analysis of profitability and solvency of PT. Adira Dinamika Multifinance Tbk, Samarinda branch uses Return On Equity, Return On Assets, Debt to Equity, and Debt to Assets analysis for 3 years, namely 2016-2018Based on the results of research and discussion of Return on Equity Profitability Analysis in 2016 by 10.4% in 2017 by 9.8% in 2018 8.3%, the value of Return on Assets in 2016-2018 decreased, in 2016 amounted to 2.5% in 2017 amounted to 2% in 2018 amounted to 1.6%. Debt to Equity increased in 2016-2018 in 2016 by 310.4% in 2017 by 392.9% in 2018 by 408.8%, Debt to Assets increased in 2016 by 75.6%, in 2017 by 79.7% in 2018 amounted to 80.3%.Profitability Level of PT. Adira Dinamika Multifinance Tbk Samarinda branch in terms of the Return On Equity ratio, and the Return On Assets Ratio in 2016-2018 has decreased in number, which means the performance has decreased in 2017-2018 Return On Equity has decreased which means the performance has decreased. Solvency Level of PT. Adira Dinamika Multifinance Tbk Samarinda branch in terms of the ratio of Debt to Equity Ratio and Debt To Assets Ratio in 2016-2018 experienced an increase in numbers, which means the performance has decreased